Rapidly and Repeatedly Reprogrammable Liquid Crystalline Elastomer via a Shape Memory Mechanism. Issue 21 (28th April 2022) - Chen, Guancong; Jin, Binjie; Shi, Yunpeng; Zhao, Qian; Shen, Youqing; Xie, Tao
Abstract: Realization of muscle‐like actuation for a liquid crystal elastomer (LCE) requires mesogen alignment, which is typically achieved/fixed chemically during the synthesis. Post‐synthesis regulation of the alignment in a convenient and repeatable manner is highly desirable yet challenging. Here, a dual‐phase LCE network is designed and synthesized with a crystalline melting transition above a liquid crystalline transition. The crystalline phase can serve as an "alignment frame" to fix any mechanical deformation via a shape memory mechanism, leading to corresponding mesogen alignment in the liquid crystalline phase. The alignment can be erased by melting, which can be the starting point for reprogramming. This strategy that relies on a physical shape memory transition for mesogen alignment permits repeated reprogramming in a timescale of seconds, in stark contrast to typical methods. It further leads to unusual versatility in designing 3D printed LCE with unlimited programmable actuation modes. Abstract : A dual‐phase LCE network with a crystalline transition temperature above the liquid crystalline transition temperature is designed. The crystalline phase serves as a built‐in physical "alignment frame" via its shape memory function. Consequently, the actuation behaviors of the liquid crystal network can be conveniently and repeatedly programmed/reprogrammed within 10 s.